1998
DOI: 10.3141/1635-19
|View full text |Cite
|
Sign up to set email alerts
|

Safety Evaluation of Alternative Signal Head Design

Abstract: A before and after safety evaluation of the installation of a larger signal head design was conducted. The design consists of a 300-mm red light, a 300-mm amber light, and a 300-mm green light, all with 150-W lamps and a yellow backboard with an additional 50-mm reflective border. The signal head design was field tested in 10 urban intersections in British Columbia. The intersections were originally equipped with the standard signal head design consisting of a 300-mm 150-W red light; a 200-mm 69-W amber light,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 3 publications
1
10
1
Order By: Relevance
“…Sayed et al found that total rate of collisions was reduced by about 24% and that the rates of both fatal and injury collisions were reduced by about 16% when an improved signal head design was used at 10 urban signalized intersections in British Columbia, Canada (15). The improved signal head design used in the study comprised a 300-mm lens for green, amber, and red lights, in addition to retroreflective tape 50 mm wide on the outer edge of the backplate.…”
Section: Improved Signal Visibility At Urban Signalized Intersectionsmentioning
confidence: 98%
“…Sayed et al found that total rate of collisions was reduced by about 24% and that the rates of both fatal and injury collisions were reduced by about 16% when an improved signal head design was used at 10 urban signalized intersections in British Columbia, Canada (15). The improved signal head design used in the study comprised a 300-mm lens for green, amber, and red lights, in addition to retroreflective tape 50 mm wide on the outer edge of the backplate.…”
Section: Improved Signal Visibility At Urban Signalized Intersectionsmentioning
confidence: 98%
“…Moreover, sites with potential for improvement are usually chosen based on their recent poor safety record (as was the case in this study), resulting in RTM bias; this is a situation where the count of crashes in the "after" period will generally revert toward the expected mean value even if the site was not treated (Washington et al 2003, Abbess et al 1981, Hauer and Persaud 1983. This can overstate the effect of a treatment by 5% to 10%, depending on the length of the "before" period (Sayed et al 1998, Econometric Analysis 2004.…”
Section: Empirical Bayes Proceduresmentioning
confidence: 99%
“…Most of these studies used laboratory or controlled field testing to determine the effects of various factors, such as signal lens size, back plates, weather conditions, and driver characteristics, on the visibility of traffic signals (8)(9)(10)(11)(12). Although the literature on signal visibility is extensive, only a few studies have been conducted to determine the potential safety impacts of improvements to signal visibility (13)(14)(15)(16)(17)(18). Furthermore, many of the studies suffered a number of shortcomings caused by (a) use of simple before-and-after evaluations (13,14), (b) evaluation of a small number of locations (16), or (c) failure to detect the safety impacts on specific collision types.…”
Section: Previous Workmentioning
confidence: 99%
“…Although the literature on signal visibility is extensive, only a few studies have been conducted to determine the potential safety impacts of improvements to signal visibility (13)(14)(15)(16)(17)(18). Furthermore, many of the studies suffered a number of shortcomings caused by (a) use of simple before-and-after evaluations (13,14), (b) evaluation of a small number of locations (16), or (c) failure to detect the safety impacts on specific collision types.…”
Section: Previous Workmentioning
confidence: 99%